When the child becomes a grammarian: aspects of the conceptualization of the notion of 'sentence' - Saint-Pierre, Madeleine (Lenguas Modernas, 2017)
This article aims at describing the conceptualization of the notion of 'sentence' in children aged six to eleven, on the basis of an experimental study held in a French Canadian primary school. The main issues are: 1) the re-examination of the delimitation between the non-metalinguistic and the metalinguistic types of reasoning as put forward by Berthoud-Papandropoulou 1980; Boutet, Gauthier, Saint Pierre 1983a, b; and Christinat- Tiéche 1988; 2) the evolution of children's ability to take the sentence as an object of reflection distinct from its referent.